A call for collaboration among food systems programs in higher education to train the future workforce - Collier, Sarah M.; Ismach, Alan; Jansen, Victoria; Kiser, Aba; Henning, Holly; Lewis, Laura R.; Spiker, Marie L.; Otten, Jennifer J. (Frontiers in Sustainable Food Systems, 2024)
A well-trained food systems workforce is in high demand, and food systems education programs are proliferating in higher education. However, these programs often struggle to embody the full interdisciplinary scope of the field of food systems, in part due to the limitations of traditional academic structures. Here, we present an inventory of existing U.S. food systems educational programs which showcases the breadth of their geographic distribution and disciplinary contexts. We pair this with a case study of two geographically proximal, highly complementary programs, one at a land grant university and one within a school of public health. While the individual programs face challenges in achieving full interdisciplinarity, their pairing showcases that striking opportunities exist to augment interdisciplinarity through inter-institutional collaboration. More models of successful inter-institutional collaborative food systems education are needed. Growth in this area would be aided by external funding for proof-of-concept models, fostering learning networks across disciplinarily distinct programs, and fighting the mission creep of individual programs striving to “do it all” at the expense of quality, stability, or an appreciation for the value of diverse core strengths.